Does Social Expenditure Increase Social Welfare in Indonesia? - Permata, Santa; Khanifa, Fadhla; Bakhri, Syamsul (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research analyzes the influence of social expenditure (health, education and social protection) on HDI and the influence of social expenditure in the health sector on infant mortality rates. This research uses panel data in 33 provinces in Indonesia during the 2010-2020 periods. This research uses panel data regression estimation with a fixed effect model. The research results show that the panel data regression estimation results show that statistically the social expenditure variables (health, education and social protection) have a significant influence on HDI. The regression coefficient for government expenditure in the health sector is 0.053 units. The regression coefficient for education expenditure is 0.161 units. The regression coefficient for social protection expenditure is 0.032 units. The three independent variables X1 (health), X2 (education), and X3 (social protection) have a positive relationship with Y (HDI). This means that when social spending is increased, the HDI will increase. Statistically it is also found that social expenditure in the health sector has a significant influence on infant mortality rates. The regression coefficient for government spending in the health sector is -0.228, meaning that every 1 percent increase in government spending in the health sector will reduce the infant mortality rate by 0.228 per 1000 live births assuming the conditions of other independent variables are constant.